PENGARUH MODEL PEMBELAJARAN TEACHING GAMES FOR UNDERSTANDING DAN TEAMS GAMES TOURNAMENT TERHADAP PENINGKATAN NILAI KERJASAMA - Wikeu Putri Munarosana; Mochamad Fajar Permana; Asep Akbaruddin; Wahyu Saputra (STKIP Subang, 2024)
Education is an effort to develop both physical and spiritual potential in accordance with the values ​​of society and culture. In formal education, the subject of Physical Education, Sports, and Health (PJOK) plays an important role. The purpose of this study is to improve the value of cooperation in students of SMA YADIKA KALIJATI. The cooperative learning approach, such as Teams Games Tournament (TGT) and Teaching Games for Understanding (TGFU), is an effective model. This study uses a quantitative method. The subjects of this study were students of SMA YADIKA KALIJATI in class X, the instruments used in this study used questionnaires, interviews and documentation. Based on the results of the study on the effect of the Teaching Games For Understanding (TGFU) and Teams Games Tournament (TGT) learning models on increasing the value of cooperation in SMA Yadika Kalijati, it can be concluded that both learning models are effective in increasing the value of cooperation in students. The average pretest score for the class using the TGFU learning model was 78.23, and increased to 85.04 after treatment. Meanwhile, the average pretest score for the class using the TGT learning model was 78.50, and increased to 88.48 after treatment. These results indicate that the TGT learning model is more effective in increasing cooperation scores compared to the TGFU model